Mechanisms to Encourage Vaccination of Public and State-Funded Employees in the Autonomous Republic of Adjara - Mariam Davitadze (European Scientific Journal, ESJ, 2022)
The present article is dedicated to the discussion of such a topical issue as the mechanisms for encouraging vaccination of public and state-funded employees in the Autonomous Republic of Adjara. The paper is an observational analysis as it discusses the ongoing process of vaccination as one of the main means of combating the pandemic in Georgia and other topical issues related to it. Based on the observation of the situation in the public sector of Adjara Autonomous Republic, the advantages and disadvantages of vaccination are assessed, the risks are presented and recommendations are made for voluntary involvement of more citizens in the vaccination process. In particular, the forms of vaccination incentives for state-funded and public employees who will significantly contribute to the rapid and positive impact of vaccination are evaluated.